2012
DOI: 10.1002/ajmg.a.35590
|View full text |Cite
|
Sign up to set email alerts
|

Clinical expression in Pfeiffer syndrome type 2 and 3: Surveillance in Japan

Abstract: Pfeiffer syndrome (PS) is a classic type of craniosynostosis syndrome. Severe cases usually require emergency care at birth. However, early diagnosis is often precluded by the rarity and consequent low awareness of this disease. This study aimed to clarify phenotypic expressions useful for the diagnosis of PS. We reviewed all cases of PS type 2 or 3 according to Cohen's classification that were reported between 1980 and 2011 in Japan. Clinical and genetic information were extracted from the patients' medical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Reported cases of prenatal diagnosis are relatively rare, and detection in the fetal period is difficult, although the incidence is three to five in 10 000 live births . Most cases of craniosynostosis are compatible with survival, although a high mortality rate is observed during the neonatal period in some conditions . Careful planning of the delivery method and perinatal care is crucial because of the potential for complex anomalies of the upper airway due to midfacial hypoplasia .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported cases of prenatal diagnosis are relatively rare, and detection in the fetal period is difficult, although the incidence is three to five in 10 000 live births . Most cases of craniosynostosis are compatible with survival, although a high mortality rate is observed during the neonatal period in some conditions . Careful planning of the delivery method and perinatal care is crucial because of the potential for complex anomalies of the upper airway due to midfacial hypoplasia .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Most cases of craniosynostosis are compatible with survival, although a high mortality rate is observed during the neonatal period in some conditions. 3,4 Careful planning of the delivery method and perinatal care is crucial because of the potential for complex anomalies of the upper airway due to midfacial hypoplasia. 5 Moreover, multiple reconstructive surgeries requiring the coordination of dental and orthodontic specialists may be necessary after the infancy period.…”
mentioning
confidence: 99%
“…13 With advances in early surgical interventions, more recent estimates have ranged from 7 to 22%. 4,5 Some deaths have been attributed to complications of known malformations. However, there is also an increased risk of death due to sudden respiratory arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, mutations in FGFR2 have been linked to several reports of GIT disorders. For example, GIT malformations (e.g., intestinal malrotation and atresia) were found in 22% of 23 PS patients [Koga et al, ]. Autopsy examinations in 12 of a sample population of 135 AS showed that 9 (of these 12 patients) had several visceral anomalies of the GIT, although only 1.5% of these 135 AS patients presented with GIT clinical symptoms [Cohen and Kreiborg, ].…”
Section: Introductionmentioning
confidence: 99%